Biodegradable hybrid-structured nanofibrous membrane supported chemoprotective gene therapy enhances chemotherapy tolerance and efficacy in malignant glioma rats. (5th November 2018) - Liu, Shih-Jung; Yang, Tao-Chieh; Yang, Shun-Tai; Chen, Ying-Chun; Tseng, Yuan-Yun
Abstract: Chemotherapy is ineffective for treating malignant glioma (MG) because of the low therapeutic levels of pharmaceuticals in tumour tissues and the well-known tumour resistance. The resistance to alkylators is modulated by the DNA repair protein O 6 -alkylguanine-DNA alkyltransferase (AGT). O 6 -benzylguanine ( O 6 -BG) can irreversibly inactivate AGT by competing with O 6 -methylguanine and has been confirmed to increase the therapeutic activity of alkylators. We developed hybrid-structured poly[(d, l )-lactide- co -glycolide] nanofibrous membranes (HSNMs) that enable the sequential and sustained release of O 6 -BG and two alkylators (carmustine and temozolomide [TMZ]). HSNMs were surgically instilled into the cerebral cavity of pathogen-free rats and F98 glioma-bearing rats. The release behaviours of loaded drugs were quantified by using high-performance liquid chromatography. The treatment results were compared with the rats treated with intraperitoneal injection of O 6 -BG combined with surgical implantation of carmustine wafer and oral TMZ. The HSNMs revealed a sequential drug release behaviour with the elution of high drug concentrations of O 6 -BG in the early phase, followed by high levels of two alkylators. All drug concentrations remained high for over 14 weeks. Tumour growth was slower and the mean survival time was significantly prolonged in the HSNM-treated group. Biodegradable HSNMs can enhance therapeutic efficacy and prevent toxic systemic effects.